Design, Development and Implementation of Standalone Transmission Control Module for Mercedes-Benz 722.6 5G-Tronic Gearbox - Azman, Hakim Asyraf (2018)
Upgrading from an older 722.4 to the newer 722.6 gearbox will give a huge benefit as it gives more flexibility, fuel conservation as well as offering a higher gear ratio. The Mercedes-Benz 722.6 gearbox can be physically bolted to different Mercedes engines quite straightforwardly with some changes required in their bellhousings. However, an off-the-shelve 722.6 Transmission Control Module (TCM) cannot be used for this upgrade purpose as that particular control module is designed only for the 722.6 transmission. The best solution is to design an independent or a Standalone Transmission Control Module (STCM) that is responsible for gears shifting. Parameters such as throttle positioning and transmission speed need to be extracted from the gearbox to monitor the overall vehicle performance. The STCM is constructed from an Arduino microcontroller which will performs tasks assigned by the driver’s input as well as algorithm constructed inside. As for the expected results, the STCM is able to shift gears smoothly by engaging six numbers of control solenoids inside valve body of the gearbox and the Mercedes W124 is able to be driven like a normal automatic transmission car.